The use of supplementary materials in efl classes: a comparative analysis of public and private high schools - Vélez Lindao, John Alberto (2013)
This study is focused on analyze the use of supplementary materials in public and private high schools in Ecuador with the aim of establishing a comparison of the type and frequency of use of these materials. This study took place in a public and in a private high school to the north of Guayaquil. In each high school, five classes were observed in 8th, 9th, and 10th grade to analyze the type, pertinence, and appropriateness of used materials. At the end of each class, the teacher was interviewed to know the intention when the teacher selected the type of supplementary material and its effect on students. Also, a student from each course answered a survey with the aim to determine the preferences about the supplementary material used by the teacher in the classroom. About methods, bibliographical method was used for gathering theoretical information and analytic and descriptive methods were used to analyze the results. Finally, the results of this research showed important information where the teachers in private high schools use more frequently supplementary materials than teachers in public schools.